Housing Cultures versus Marketing Strategies: What Evolution for Housing? - Emília Malcata Rebelo (2002)
In this paper it is made a literature review concerning the different inter-related perspectives of housing analyses: in social, urban, economic, ideological, sociologic and cultural ones. These theoretical facets are related to the ways housing can be managed: as a basic need, a product, a consumption place, a place where social relationships are developed, a place of work, an investment and/or a patrimony asset. It is made a reflection about the alternative means of housing provision, as well as about the interdependencies between the economic and social aspects of the roles deserved to state and to the free market agents in the housing sector. Besides, there are analysed the effects upon the housing markets of the emergent globalisation processes and the new technologies. Finally, i1t is presented a strategic marketing approach applied to the Porto city (Portugal) that takes advantage of the housing provision market structures, of the interdependencies among the public and private agents, and of the globalisation processes. It assumes the municipal powers leadership of urban marketing, simultaneously assuring better conditions for the free market agents performance. It defines a urban marketing policy aimed not only to identify the specific housing needs, but also to organise the rationale to give them the appropriate answer. Complementary, the real estate marketing is used to create symbolic housing representations, with architectural, environment and individual equipment aimed to specific segments of population. It strongly reinforces the urban feelings of personal and social involvement, promotes a better quality of life, and is the appropriate way to give special answers to particular housing needs.